The Routledge Handbook of Language Revitalization - NFN Nazarudin (Linguistik Indonesia, 2021)
Title         : The Routledge Handbook of Language RevitalizationEditor       : Leanne Hinton, Leena Huss, Gerald RocheISBN        : 978-1-315-56127-1 (e-book)Publisher  : Routledge, 2018, pp. 552